Comparison of the feasibility and validity of a one-level and a two-level erector spinae plane block combined with general anesthesia for patients undergoing lumbar surgery - Zheng, Shaoqiang; Zhou, Yan; Zhang, Wenchao; Zhao, Yaoping; Hu, Lin; Zheng, Shan; Wang, Geng; Wang, Tianlong (Frontiers in Surgery, 2023)
Background: Spinal surgery causes severe postoperative pain. Erector spinae plane (ESP) block can relieve postoperative pain, but the optimal blocking method has not been defined. The aim of the study is to compare the feasibility of one-level and two-level lumbar ESP block, and their effect on intraoperative and postoperative analgesia in lumbar spinal surgery. Methods: 83 adult patients who were scheduled for posterior lumbar interbody fusion were randomly divided into two groups. Patients in Group I (n=42) received ultrasound-guided bilateral one-level ESP block with 0.3% ropivacaine, while patients in Group II (n=41) received bilateral two-level ESP block. Blocking effectiveness was evaluated, including whether sensory block covered surgical incision, sensory decrease in anterior thigh, and quadriceps strength decrease. Intraoperative anesthetic dosage, postoperative visual analogue scale scores of pain, opioid consumption, rescue analgesia, and opioid-related side effects were analyzed. Results: 80 patients finished the clinical trial and were included in the analysis, with 40 in each group. Time to complete ESP block was significantly longer in group II than in group I (16.0 [14.3, 17.0] min vs 9.0 [8.3, 9.0] min, P=0.000). The rate of sensory block covering surgical incision at 30 min was significantly higher in Group II than in Group I (100% [40/40] vs 85.0% [34/40], P=0.026). The rate of sensory block in anterior thigh was higher in Group II (43.8% [35/80] vs 27.5% [22/80], P=0.032), but the rate of quadriceps strength decrease did not differ significantly between groups. The mean effect-site remifentanil concentration during intervertebral decompression was lower in Group II than in group I (2.9±0.3 ng/ml vs 3.3±0.5 ng/ml, P=0.007).There were no significant differences between groups regarding intraoperative analgesic consumption, postoperative analgesic consumption, and postoperative VAS pain scores at rest and with movement within 24 hours. There was no block failures, block-related complications and postoperative infection. Conclusions: Among patients undergoing posterior lumbar interbody fusion, two-level ESP block provided higher rate of sensory block covering surgical incision when compared with one-level method, without increasing the incidence of procedure-related complications.